Evaluation of biological markers for the risk assessment of carbon black in epidemiological studies - Yong, Mei; McCunney, Robert J. (Frontiers in Public Health, 2024)
Background/Objectives Engineered nanomaterials (ENMs) have been suggested as capable of promoting inflammation, a key component in the pathways associated with carcinogenesis, cardiovascular disease, and other conditions. As a result, risk assessment of biological markers as early stage indicators has the potential to improve translation from experimental toxicologic findings to identifying evidence in human studies. The aim of the study is to review the possible early biological changes in workers exposed to Carbon Black (CB), followed by an evidentiary quality evaluation to determine the predictive value of the biological markers.We conducted literature search to identify epidemiological studies that assessed biological markers involved in the inflammatory process at early stages among the workers with exposure to CB. We reviewed the studies regarding study design, statistical analyses, findings, and limitations.We identified five Chinese studies that investigated the potential impact of exposure to CB on inflammatory markers, bronchial wall thickening, genomic instability, and lung function impairment in CB production workers. Of the five Chinese studies, 4 were cross-sectional; another study reported results at two time points over 6 years of follow-up. The authors of all 5 studies concluded positive relationships between exposure and the inflammatory cytokines profiles. Weak to very weak correlations between biomarkers and early stage endpoints were reported.Conclusions Most inflammatory markers failed to satisfy proposed evidentiary quality criteria. The significance of the results of the reviewed studies is limited by crosssectional study design, inconsistency in results, uncertain clinical relevance, and the high occupational exposures. Based on this review, risk assessment relying on the inflammatory markers does not seem appropriate at this time. Nevertheless, the novel research warrants further exploration in assessing exposure to ENMs and corresponding potential health risks in occupational settings.